Mother's education and the risk of several neonatal outcomes: an evidence from an Italian population-based study - Anna Cantarutti; Matteo Franchi; Matteo Monzio Compagnoni; Luca Merlino; Giovanni Corrao (BMC, 2017)
Abstract Background Maternal socioeconomic disparities strongly affect child health, particularly in low and middle income countries. We assessed whether neonatal outcomes varied by maternal education in a setting where healthcare system provides universal coverage of health services to all women, irrespective of their socioeconomic status. Methods A population-based study was performed on 383,103 singleton live births occurring from 2005 to 2010 in Lombardy, an Italian region with approximately 10 million inhabitants. The association between maternal education, birthplace and selected neonatal outcomes (preterm birth, low birth weight, small-for-gestational age, low 5-min Apgar score, severe congenital anomalies, cerebral distress and respiratory distress) was estimated by fitting logistic regression models. Model adjustments were applied for sociodemographic, reproductive and medical maternal traits. Results Compared with low-level educated mothers, those with high education had reduced odds of preterm birth (Odds Ratio; OR = 0.81, 95% CI 0.77-0.85), low birth weight (OR = 0.78, 95% CI 0.70-0.81), small for gestational age (OR = 0.82, 95% CI 0.79-0.85), and respiratory distress (OR = 0.84, 95% CI 0.80-0.88). Mothers born in a foreign country had higher odds of preterm birth (OR = 1.16, 95% CI 1.11-1.20), low Apgar score (OR = 1.18, 95% CI 1.07-1.30) and respiratory distress (OR = 1.19, 95% CI 1.15-1.24) than Italian-born mothers. The influence of maternal education on neonatal outcomes was confirmed among both, Italian-born and foreign-born mothers. Conclusions Low levels of education and maternal birthplace are important factors associated with adverse neonatal outcomes in Italy. Future studies are encouraged to investigate factors mediating the effects of socioeconomic inequality for identifying the main target groups for interventions.